1993
DOI: 10.1111/j.1365-2125.1993.tb04202.x
|View full text |Cite
|
Sign up to set email alerts
|

R‐verapamil: pharmacokinetics and effects on PR interval, blood pressure and heart rate.

Abstract: 1. This study in healthy normotensive male volunteers investigated the pharmacokinetics and the effects on electrocardiographic PR interval, blood pressure and heart rate of single oral doses of the single isomer R‐verapamil (250, 500 and 1000 mg) in comparison to placebo and 240 mg racemic verapamil. 2. After 500 and 1000 mg R‐verapamil there were significant prolongations in PR interval, maximal at 1‐2 h after dosing and coincident with peak plasma drug concentrations, but these were not significantly differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
(19 reference statements)
1
6
0
Order By: Relevance
“…Following intravenous dosing of racemic verapamil, Abernethy et al also noted that while the plasma clearance and volume of distribution for R-and S-verapamil varied, the elimination halflife was 3 h for both enantiomers [15]. Similarly, Ahmed et al did not observe a difference in halflife following 250, 500, or 1000 mg R-verapamil [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following intravenous dosing of racemic verapamil, Abernethy et al also noted that while the plasma clearance and volume of distribution for R-and S-verapamil varied, the elimination halflife was 3 h for both enantiomers [15]. Similarly, Ahmed et al did not observe a difference in halflife following 250, 500, or 1000 mg R-verapamil [16].…”
Section: Discussionmentioning
confidence: 99%
“…CRverapamil was administered orally during four sequential 5-day dosing periods with no intervening washout periods. Subjects were randomized to one of two sequences: Sequence A = 120 mg (Days 1-5), 180 mg (Days 6-10), 360 mg (Days 11-15), and 540 mg ( Days [16][17][18][19][20]; Sequence B = 180 mg (Days 1-5), 120 mg (Days 6-10), 360 mg (Days 11-15), and 540 mg (Days [16][17][18][19][20]. Blood samples were obtained daily prior to dosing and 2, 3,4,5,6,8,10,12,14,16,20, and 24 h after dosing on Days 1, 5, 10, 15, and 20.…”
Section: Clinical Trialsmentioning
confidence: 99%
“…To evaluate the impact of talinolol coadministration, we compared the pharmacokinetics of this study with the results reported by Ahmed et al 33 That study investigated the pharmacokinetics of R ‐verapamil after oral administration without comedication in humans and reported mean AUC values of verapamil and norverapamil of 1707 ± 774 ng · h · mL −1 and 1203 ± 462 ng · h · mL −1 , respectively, after 250 mg R ‐verapamil. In this study we calculated a mean verapamil AUC(0–24) of 507 ± 147 ng · h · mL −1 and a mean norverapamil AUC(0–24) of 1131 ± 261 ng · h · mL −1 after 120 mg R ‐verapamil.…”
Section: Discussionmentioning
confidence: 99%
“…Even in the population‐based setting, prevalence of PR prolongation increases exponentially with age, from 0.7%–2% in young, healthy subjects to up to 14% in subjects in their 80s 2. It is more commonly seen among young athletes3–6 and with a number of clinical conditions (eg, autoimmune diseases,7,8 electrolyte disturbances,9 and primary cardiac pathologies10) and is affected by pharmacological interventions11,12 and alcohol consumption,13,14 as well as ethnic differences 14. In the young it is often associated with increased vagal tone and is reversible,1,2 whereas etiology in older subjects is likely to be degenerative, with coexisting conduction system disease 15…”
Section: Introductionmentioning
confidence: 99%